X-ray fluorescence spectrometric determination of heavy metals in selected rice samples sold on the Liberian market: a case study conducted in Paynesville City, Greater Monrovia - James, McClain; Plenseh Diana, PAYE; Kokolo , N’debewillie; Sampson K. P., CHEA; J. Boima, Kiazolu (International Journal of Basic and Applied Sciences, 2022)
Background: Environmental pollution with toxic heavy metals can be lead to the possible contamination of rice. Rice is a staple food widely consumed in the urban and rural parts of Liberia daily. Rice is cultivated in approximately 113 countries and a fundamental source for energy and protein. Objective: The study assesses selected heavy metals (As, Pb, Cd, Se, and Cr) concentration in selected imported rice and traditionally grown rice and bulgur wheat in Liberia. Methods: Six grade of imported rice, Bulgar wheat, and traditionally grown rice were purchased from the Duport Road and Red-Light markets in Greater Monrovia and analyze using X-ray Fluorescence Spectrometer. All data were analyzed using XLSTAT, and data was used to calculate the risk factor of each rice sample. Results: The mean concentration of heavy metal found in the rice as follow: As, 1.31ppm; Cd, 9.42ppm; Cr. 12.3ppm; Se, 5.73ppm; and Pb, 1.75ppm. The estimated daily intakes (EDIs) were calculated in combination with the rice consumption data. The mean intakes of As, Cd, Cr, Se, and Pb through rice were estimated to be 1.32, 9.42. 12.4. 5.74, and 1.75 mg/kg BW/day. Chromium has the average estimated daily intake. The combined hazard index for the heavy metals in each sample and the total cancer risk for each sample contributed most significantly to a cancer risk of rice consumption during adult life expectancy.Conclusion: The selected heavy metal concentration from the rice sample was above the FAO/WHO reference Standard but was within the range of the contaminant level except for chromium, which is above the accepted range. However, the hazard index and the total cancer risk indicate a potential non-carcinogenic and carcinogenic risk.
Keywords: Duport Road; Red-light; EDI; Greater-Liberia; XRF; Rice.